The influence of positive work attitude and emotion on intention to leave among ICT professionals in Malaysia / Safiah Omar - Omar, Safiah (Institute of Graduate Studies, UiTM, 2016)
The disequilibrium growth between the skills supplies and the growth of technologies raise a concern for this study to carry out research in the area of intention to leave among the ICT Professionals in Malaysia. This is due to the statistics report on the high rate of turnover in the ICT industry. At the same time the role of the ICT industry is also very important in contributing to the growth of the country. Two types of intention to leave were tested in this study which is the intention to leave the organization and the intention to leave the career. A considerable amount of literature has been published on intention to leave but mostly studied from the negative perspectives such as job dissatisfaction, burnout, work conflicts, psychological distress, and employee disengagement. This study answering the call from the positive psychology movement where the study area focus on positive side and the strengths of individual such as positive work attitude and work emotion in determining the factors to reduce the levels of intention to leave. The constructs are career commitment, positive organizational behaviour (POB), work happiness as mediator, and career adaptability as moderator. Using questionnaires as the main assessment instruments, this study adopts quantitative approach for the analyses and using mainly on structural equation modelling (SEM). Confirmatory factor analyses (CFA) were conducted among all the constructs prior to the hypothesized testing. Results from the CFA suggested that the hypothesized framework needed to be separated between intention to leave the organization and intention to leave the career…